Prevención de Caídas: Mantenerse Activo - Sergio Romero (EDIS)
Revised! FCS2232-Span, a 4-page fact sheet by Sergio Romero, is the Spanish Language version of "Fall Prevention: Staying Active." It describes directions for several exercises which can help people maintain or improve balance, strength, and flexibility. Published as part of the Elder Nutrition and Food Safety (ENAFS) program by the UF Department of Family Youth and Community Sciences, May 2006.